The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.urology.2013.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selective Parenchymal Clamping to Hilar Clamping During Robotic-assisted Laparoscopic Partial Nephrectomy

Abstract: OBJECTIVE To compare perioperative outcomes after robotic-assisted laparoscopic partial nephrectomy (RALPN) with hilar clamping vs parenchymal clamping. METHODS A retrospective, single-institution review of the patients undergoing RALPN with hilar or parenchymal clamping was performed. Associations between perioperative factors and clinicopathologic outcomes were determined using the t test, Fisher’s exact test, and multivariate linear regression. RESULTS In 51 patients undergoing RALPN, 36 (71%) and 15 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…WIT reduction techniques have expectedly led to better PRF recovery. 6,7,18 However, the safe duration of ischemia during PN remains controversial. 19e21 Several studies indicated that ischemia time has a secondary role and the quantity of preserved nephrons is the primary determinant of ultimate renal function after PN.…”
Section: Discussionmentioning
confidence: 99%
“…WIT reduction techniques have expectedly led to better PRF recovery. 6,7,18 However, the safe duration of ischemia during PN remains controversial. 19e21 Several studies indicated that ischemia time has a secondary role and the quantity of preserved nephrons is the primary determinant of ultimate renal function after PN.…”
Section: Discussionmentioning
confidence: 99%
“…Off-clamp PN and parenchymal compression are both novel techniques being utilized which aim to avoid hilar clamping entirely (43). Regional ischemia by way of a parenchymal clamp or tourniquet may be feasible when the anatomy allows, particularly in the case of tumors in polar locations.…”
Section: Ischemiamentioning
confidence: 99%
“…Loss of renal function occurs if the duration of warm ischemia is >28 min (5). A number of techniques have been developed with the aim of minimizing warm ischemic injury (2,6,7). The technique of renal segmental artery clamping involves the selective clamping of renal arterial branches, and may eliminate renal ischemia from the entire kidney and minimize renal functional loss (4).…”
Section: Introductionmentioning
confidence: 99%